2010
DOI: 10.1095/biolreprod.109.081570
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation in the Absence of the Ovarian Surface Epithelium in the Primate1

Abstract: The ovarian surface epithelium (OSE) has a prominent role in ovarian cancer in women, but no studies have been conducted to evaluate its role in normal ovarian function. Data from other species suggest the OSE is needed for ovulation. We have tested whether the OSE is needed for follicle rupture, a necessary step in ovulation, using the nonhuman primate, rhesus macaque. The OSE was removed in two different short-term protocols spanning a single periovulatory interval--one protocol used a cytology brush to remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Considering that tumours often take decades until they manifest (Beerenwinkel et al, 2007), FE cells that have repopulated ruptured ovarian surface epithelia might thus be the culprits for later tumour development in some cases. Ovulation itself which, at least in primates, does not require the OSE (Wright et al, 2010), may further contribute to ovarian carcinogenesis via free radicals in the follicular fluid and via inflammatory mediators released in response to follicular rupture and during tissue repair (Murdoch and Martinchick, 2004). This is in complete agreement with epidemiological data showing that women who have used ovulation-inhibiting oral contraceptives over a number of years bear a reduced risk of developing ovarian cancer (Ory, 1987;Beral et al, 2007).…”
supporting
confidence: 61%
“…Considering that tumours often take decades until they manifest (Beerenwinkel et al, 2007), FE cells that have repopulated ruptured ovarian surface epithelia might thus be the culprits for later tumour development in some cases. Ovulation itself which, at least in primates, does not require the OSE (Wright et al, 2010), may further contribute to ovarian carcinogenesis via free radicals in the follicular fluid and via inflammatory mediators released in response to follicular rupture and during tissue repair (Murdoch and Martinchick, 2004). This is in complete agreement with epidemiological data showing that women who have used ovulation-inhibiting oral contraceptives over a number of years bear a reduced risk of developing ovarian cancer (Ory, 1987;Beral et al, 2007).…”
supporting
confidence: 61%
“…Studies have found almost 90% of ovarian cancer originates from the ovarian surface epithelium (mesothelium) that invaginates into the underlying stroma resulting in inclusion cysts that eventually undergo malignant transformation [25][26][27]29] . As a result, Wright et al [30] think that if the OSE is removed, the risk for developing ovarian cancer can be greatly reduced, [31] used a rhesus monkey model to extend observation time to 6 months and 12 months after removal of the OSE and obtained similar results. This study provides a new strategy for preventing ovarian cancer.…”
Section: Ovarian Surface Epithelial Stem Cells Can Undergo Neo-oogenementioning
confidence: 87%
“…Fixed ovaries were paraffin embedded and cut into 5 mm sections as described previously (Wright et al, 2010) for hematoxylin and eosin (H&E) or immunohistochemical (IHC) staining. H&E labeled sections were used to examine OSE morphological characteristics: height, lateral density and presence or absence of an apical projection.…”
Section: Ose Histology Immunohistochemical Labeling and Analysismentioning
confidence: 99%